STRENGTH-DURABILITY PROPERTIES AND MICROSTRUCTURAL ANALYSIS OF CONCRETE CONTAINING COW BONE ASH AND BENTONITE - Awoyemi, T. J.; Ibedu, Kenneth Ejike; Kaura, J. M.; Lawan, A. (FUDMA JOURNAL OF SCIENCES, 2023)
One of the major agricultural wastes discarded from abattoirs in large quantities is the cow bone. Thus, there is need to find alternative means of promoting cleaner environment which is critical for environmental sustainability. This study aims to establish the viability of using cow bone ash and bentonite as partial replacement for cement improve the properties of concrete. Chemical composition examined on the CBA and BT showed that the materials have potential to serve as supplementary cementing material in concrete. In this study cement was partially replaced with cow bone ash and bentonite at 5% interval from 5 – 20%. Mix with 10% CBA/BT had the highest compressive strength across all curing ages. At 7, 14, 21, 28 and 56days 10% CBA/BT replacement recorded a 1, 49, 23, 14 and 8% increase in compressive strength respectively, similar flexural and split tensile strength examined also showed increase in strength. Water absorption test recorded a decrease in water absorption as the CBA/BT content increased. Acid resistance test showed that the concrete specimen reduced in compressive strength of at an average of 39%. The microstructure analysis of the concrete specimen revealed an improved micro packing of aggregate resulting in a denser and increased strength of concrete. The study finds that at optimal dosage of 10% CBA/BT, the concrete had an improved mechanical strength, lower water absorption ability and a better interlocking particle arrangement at microstructural level.